Robotic-Assisted Bladder Neck Procedures for Incontinence in Pediatric Patients - Gargollo, Patricio C.; White, Lindsay A. (Frontiers in Pediatrics, 2019)
Purpose: To review the current status of bladder neck procedures for incontinence in pediatric patients, focusing on the increasing role of robotic-assisted laparoscopic surgical techniques. Methods: A comprehensive review of the literature on open and robotic-assisted bladder neck procedures was conducted, with a focus on articles published in the last 20 years. This data was subsequently compared with published results from robotic-assisted bladder neck reconstruction series completed at our institution. Results: The principle bladder neck procedures for incontinence in pediatric patients include: Artificial Urinary Sphincter, Bladder Neck Sling, Bladder Neck Closure and Bladder Neck Reconstruction. Continence rates range from 60-100% with a lack of expert consensus on the preferred procedure (or combination of procedures). Robotic-assisted approaches are associated with longer operative times, especially early in the surgical experience, but demonstrate equivalent continence rates with potential benefits including: low interoperative blood loss, improved cosmesis and decreased intra-abdominal adhesion formation. Conclusions: Robotic-assisted procedures of the bladder neck are safe, feasible, follow the same steps and principles as those of open surgery and produce equivalent continence rates. Robotic-assisted techniques can be adapted to a variety of bladder neck procedures and safely expanded to selected patients with previous open abdominal surgery.